POTRET MAD'U DI RUANG DIGITAL: INTEGRASI KARAKTERISTIK AUDIENS DAN OPTIMALISASI PLATFORM MEDIA SOSIAL - Gian Widayoko; Sugeng Dwi Harianto; Abdul Basit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The contemporary era is marked by a revolutionary shift in how individuals interact, search for, and process information, a phenomenon fundamentally reshaping the landscape of disseminating religious values and narratives. The methodology employed in this research is qualitative. The findings establish that the core strategy for optimizing digital dakwah (Islamic propagation) involves transitioning the mad'u (audience) from passive consumers to active contributors through the strategic leverage of interactive platform features. Specifically, the utilization of native tools like Q&A and polling serves as a real-time diagnostic mechanism for grasping audience concerns, while Utilizing Live Sessions and Real-Time Dialogues is vital for cultivating intimacy and trust. Furthermore, the User-Generated Content (UGC) Strategy is identified as the most effective form of viral marketing, empowering the audience to act as mini-propagators by replicating the message in their own voice and format. For this to succeed, da'i (preachers) must devise Structured and Ethical UGC Campaigns to ensure the message's exponential reach. This optimization model is further strengthened by Closed Community Features such as Telegram or Discord, which function as a "digital classroom" for deep retention and tarbiyah (Islamic education), thereby fostering a strong sense of belonging and long-term loyalty. Overall, through a systematic combination of interactivity, driven UGC, and fortified closed communities, this model guarantees that dakwah in the digital domain achieves broad coverage via invaluable algorithmic signals from UGC, all while maintaining robust communal roots necessary for sustainable social-personal transformation.